دور السوق المالية في تفعيل النمو الاقتصادي والتجارة الخارجية - شرف, سمير; شعبان, إسماعيل; اسبر, هدى (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول البحث دراسة السوق المالية في تفعيل النمو الاقتصادي بشكل عام والتجارة الخارجية بشكل خاص, من خلال إظهار علاقة الأسواق المالية بالنمو الاقتصادي، ودور الرقابة على الاستثمارات في ذلك, وكذلك أثر التحرير المالي على النمو الاقتصادي من خلال المعاملات الدولية ,كما بينّ البحث عوامل جذب الاستثمار الأجنبي من خلال المؤشرات التي تبين ترتيب الدول العربية فيها, ولكي تتحقق الفائدة المرجوة من البحث تم اختبار مصداقية التحليل النظري للبحث من خلال إعداد نموذج رياضي وإحصائي لقياس العلاقة بين حركة التداول للأوراق في الأسواق الناشئة, وتأثيراتها إيجاباً أوسلباً على تفعيل حركة التجارة الخارجية This research takes into consideration the role of "Financial Market" in activating economic growth in general and foreign trade in particular by showing the relationship of Financial Markets with economic growth and the role of investment supervision in it. Also, it considers the effects of finance liberation on economic growth throughout international transactions. So, the research indicates the factors which attract foreign investments. To obtain the aspired advantages from this research, the reliability of the research theoretical analysis was tested by setting up a mathematical and statistical model for measuring the relationships between financial paper circulations in arising (young) Markets and their negative /positive effects on activating foreign trade transactions.